Effect of different feeds on growth and fecundity in ornamental fish, Betta splendens (Regan) - James, R; Sampath, K (Indian Journal of Fisheries, 2011)
Feed intake, conversion and fecundity of an ornamental fish Betta splendenswere studied as a function of feed types. Fish fed with the mixed diet and livershowed higher feeding rates followed by those fed with Artemia sp. Conversionrate and efficiency were maximum in fish fed with earthworm followed by thosewith Artemia sp. Fish fed with pelleted feed did not sexually mature and spawn,whereas, those maintained on other groups spawned thrice during the experimentalperiod. The fecundity of B. splendens fed with various types of feed decreasedin the following order : Artemia sp. > mixed diet > liver > earthworm.The number of eggs laid increased with increase in the number of spawning inall groups. The perecentage hatching of eggs in fish fed with Artemia sp., mixeddiet and liver did not vary much and it averaged 94.3%. Adult Artemia sp. andmixed diets were found suitable for enhancing reproductive performance in B.splendens.